2014
DOI: 10.2147/ccid.s44371
|View full text |Cite
|
Sign up to set email alerts
|

Cryolipolysis for noninvasive body contouring: clinical efficacy and patient satisfaction

Abstract: In recent years, a number of modalities have become available for the noninvasive reduction of adipose tissue, including cryolipolysis, radiofrequency, low-level laser, and high-intensity focused ultrasound. Each technology employs a different mechanism of action to cause apoptosis or necrosis of the targeted adipocytes. Among these technologies, cryolipolysis has not only been commercially available for the longest time, but has also been best researched including in vitro and animal models and randomized con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(24 citation statements)
references
References 26 publications
0
20
0
1
Order By: Relevance
“…It has a major difference from other modalities such as ultrasound, radiofrequency, etc. (11). The principle of cryolipolysis is based on higher sensitivity of adipocytes to cold in comparison with other water-rich cells (39).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…It has a major difference from other modalities such as ultrasound, radiofrequency, etc. (11). The principle of cryolipolysis is based on higher sensitivity of adipocytes to cold in comparison with other water-rich cells (39).…”
Section: Resultsmentioning
confidence: 99%
“…The treatment session usually takes one hour (5, 7). Despite the fact that there are not any considerable changes in body fat instantly after the treatment session, different studies proved the efficacy of the procedure on reducing subcutaneous adipose tissue over time (11). In a prospective human clinical study, Dover et al revealed a decrease in lateral flank and back fat following cryolipolysis.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, despite many individual – often only anecdotal – user reports, only a minority of methods is proven according to the evidence-based medicine standards. Such evidence is available for efficacy of chemical lipolysis, based on injection of phosphatidylcholine and deoxycholic acid 9 , and for selected energy-based technologies using focused ultrasound 10 , cryolipolysis 11 and/or thermal/radiofrequency for lipolysis 12 . Despite the broad use in the practice, clinical safety data of these aesthetic procedures are scarce, with only a few publications available 13 .…”
Section: Introductionmentioning
confidence: 99%